Mineral Feed Grinding Performance of Drum Mills - P. V. Malyarov (International Mineral Processing Congress, 2018)
"This paper examines the grinding and wear processes in drum mills. A summary of the industry’s long-term experience with the proposed linings is presented. A method is proposed for assessing the efficiency of the grinding energy distribution between the successive stages. A case study is presented of grinding energy redistribution at Talnakh Concentrator by replacing spiral classifiers with a drum-type hydraulic screen. The problems of the kinetics of grinding processes in ball mills and semi-autogenous (SAG) mills are examined. It is demonstrated that in ball mills the feed particles are disintegrated by triaxial compression in the mill zones where discrete slippage of the charge occurs at major force interactions between the layers. Mechanism underlying increases in the specific energy consumption in grinding circuits based on SAG mills is shown.The problem of improving the throughput and reducing the specific energy consumption in mineral feed grinding is highly relevant because of the significant energy intensity. Up to 80% of the consumed energy is used to disintegrate ore fed into the drum mill. At all development stages of the drum mill grinding theory, the researchers have paid a great deal of attention to studying the patterns of the charge motion and the kinetics of the feed particles disintegration processes. In [1], it was shown that, due to the slippage between the charge layers being lifted, drum mills at concentrator plants operate in a mixed cascade and waterfall mode. A feature of the mixed mode is the toe zone, where the charge contacts the lining and the transition to a circular path takes place. Studies of the charge motion in the toe zone made it possible to develop a method for designing cross-sectional profiles of lining plates [2] for ball mill drums. The method is based on the principle of interaction between the balls and the lining, where the non-working rear surfaces follow the relative motion path of the balls before impacting the lining, while the working surfaces are orthogonal to the rear ones. Lining with the proposed profile provides contact with the charge and slippage-free transition to a circular path. This ensures an longer service life of the lining, a reduction in specific energy consumption, and an increase in the mill’s feed rate. The proposed method is applicable when designing lining plates of various materials. Steel liners with the proposed profile have been successfully operated [3] for more than 40 years at a number of projects in the industry."